Una critica del concetto di intenzionalità in Husserl alla luce della metapsicologia freudiana - Dalto, Silvana (Metapsychologica - rivista di psicanalisi freudiana, 2024)
A criticism of the concept of intentionality in Husserl in the light of Freudian metapsychology. A criticism of Brentano’s and Husserl’s concept of intentionality is carried out and a comparison is made with Freud’s concept of drive. For Husserl, against positivistic logic, a new approach is needed, which considers reality no longer as a set of objects separate from the subject, but which places the world as a correlate of consciousness; some inconsistencies in Husserlian argumentation are highlighted: first of all, the epoché fails to separate the self-perception from the sensitive perception; this means that the epoché is not sufficient to establish the transcendental subject, but neither is it sufficient to construct a valid objectivity in subjectivity. For Freud instead the self-position of the subject is original and arises well before the object is constituted as such. In fact the drive is originally without an object: there is nothing pre-constituted in the definition of the subject or even of our relationship with the world. The concept of drive is much more adherent to real psychic dynamics than the concept of intentionality, which is moreover contradicted by basic clinical phenomena such as anxiety or hallucination.